Dimerized ground states in spin-S frustrated systems - Lamas, Carlos Alberto (2015)
We study a family of frustrated antiferromagnetic spin-S systems with a fully dimerized ground state. Starting from the simplest case of the frustrated zigzag spin ladder, we generalize the family to more complex geometries like tetrahedral ladders and spin tubes. After presenting some numerical results about the phase diagram of these systems, we show that the ground state is robust against the inclusion of weak disorder in the couplings as well as several kinds of perturbations, allowing to study some other interesting models as a perturbative expansion of the exact one. A discussion on how to determine the dimerization region in terms of quantum information estimators is also presented. Finally, we explore the relation of these results with the case of a four-leg spin tube, which recently was proposed as a model for the description of the compound Cu2Cl4D8C4SO2, delimiting the region of the parameter space where this model presents dimerization in its ground state.